The Influence of HIV/AIDS Literacy in Pregnant Women on Willingness to Undergo PMTCT Examination in Pematangsiantar City, North Sumatra, Indonesia - Safrina Safrina; Sri Hernawati Sirait; Tinuk Esti Handayani; Ayesha Hendriana Ngestiningrum (Knowledge Dynamics, 2024)
Background: In 2019, 2,370,473 pregnant women in Indonesia were tested for HIV, with 6,439 (0.27%) testing positive. Despite the importance of HIV testing during pregnancy to prevent mother-to-child transmission of HIV (PMTCT), not all pregnant women are willing to undergo testing. This study aims to evaluate the impact of health literacy about HIV/AIDS on pregnant women’s willingness to participate in PMTCT examinations in Pematangsiantar City. Methods: A quasi-experimental design with pretest and posttest, including a control group, was employed. The study population comprised pregnant women in Pematangsiantar City who had not undergone voluntary counseling and testing (VCT). A total of 102 participants (51 in the experimental group and 51 in the control group) were selected based on specific inclusion and exclusion criteria through consecutive sampling. Health literacy was measured using the Indonesian version of the health literacy questionnaire (HLS-EU-SQ10-IND). Data were analyzed using the McNemar test with a significance level set at p < 0.05. Results: In the HIV/AIDS literacy group, 32 participants (62.7%) were willing to undergo PMTCT, whereas in the control group, 32 participants (62.7%) were not willing. The literacy group showed significant improvements in willingness to undergo PMTCT after receiving information, with p-values of 0.012 (overall), 0.003 (understanding), 0.021 (assessing), and 0.007 (implementing). Conversely, the control group did not show significant changes, with p-values of 0.375, 0.210, 0.063, and 0.227, respectively. Conclusion: Health literacy about HIV/AIDS significantly enhances pregnant women’s willingness to participate in PMTCT. Increased counseling and information from health workers are crucial for improving PMTCT coverage.